Stigma, Shame and Women's Limited Agency in Help-Seeking for Intimate Partner Violence - McCleary-Sills, Jennifer (Taylor and Francis, 2015)
In Tanzania, 44% of women experience intimate partner violence (IPV) in their lifetime, but the majority never seeks help, and many never tell anyone about their experience. Even among the minority of women who seek support, only 10% access formal services. Our research explored the social and structural barriers that render Tanzanian women unable to exercise agency in this critical domain of their lives. We collected qualitative data in three regions of Tanzania through 104 key informant interviews with duty bearers and participatory focus groups with 96 male and female community members. The findings revealed numerous sociocultural barriers to help-seeking, including gendered social norms that accept IPV and impose stigma and shame upon survivors. Because IPV is highly normalised, survivors are silenced by their fear of social consequences, a fear reinforced by the belief that it is women’s reporting of IPV that brings shame, rather than the perpetration of violence itself. Barriers to help-seeking curtail women’s agency. Even women who reject IPV as a ‘normal’ practice are blocked from action by powerful social norms. These constraints deny survivors the support, services and justice they deserve and also perpetuate low reporting and inaccurate estimates of IPV prevalence.